Developmental delay and its predictors among children under five years of age with uncomplicated severe acute malnutrition: a cross-sectional study in rural Pakistan - Javeria Saleem; Rubeena Zakar; Gul Mehar Javaid Bukhari; Aneela Fatima; Florian Fischer (BMC Public Health, 2021)
Abstract Background In developing countries, malnutrition in children and developmental delays are two major challenges for public health. To achieve the vision of the Sustainable Development Goals from the broader perspective of child health, early identification of developmental delays and timely intervention are crucial. The aim of this study is to assess the prevalence of suspected developmental delay and their predictors in children under the age of 5 years with uncomplicated severe acute malnutrition in rural areas of Pakistan. Methods A multicentre cross-sectional study was conducted among 185 children with uncomplicated severe acute malnutrition. We screened children aged 6–59 months for their nutritional status and clinical complications. Children fulfilling the inclusion criteria underwent the Denver Development Screening Tool II (DDST-II). The children’s global developmental profile was calculated according to the established protocols of DDST-II, which are based on four important domains of development: personal and social behaviour, language, gross motor adaptive skills and fine motor adaptive skills. A pretested questionnaire was used to collect data on socio-demographic and nutritional factors for assessing predictors of developmental delay, which were analysed using a multivariate logistic regression model. Results Out of 177 children with severe acute malnutrition, 69 (38.9%) had normal global development and 108 (61.1%) had delayed global development. Significant associations were found between global developmental delay and younger children (6–24 months vs. 25–59 months; AOR = 4.53, 95% CI: 1.56–13.10, p < 0.01), children who were not exclusively breastfed (AOR = 3.07, 95% CI: 1.24–7.56, p = 0.01), and a history of contact with a tuberculosis smear-positive adult (AOR = 2.67, 95% CI: 1.30–5.49, p < 0.01). Conclusion About two thirds of the study participants showed delayed or unstable global development. Thus, according to DDST-II-established protocols, there is a high prevalence of suspected developmental delay among children under the age of five years with uncomplicated severe acute malnutrition in rural areas of Pakistan. Children in their first 2 years of life were at particularly high risk due to insufficient breastfeeding. This emphasizes the need to provide adequate infrastructure and information to parents for the prevention of developmental delay in remote areas.